17 The effects of a yeast fermentation product on the average daily gain and digestibility on a rye grass hay based finishing diet for lambs. (29th July 2019) - Burt, Justin C; Boyd, Jamie; Garcia, Ivan; Splan, Rebecca; Perron, Brittany S
Abstract: The purpose of this study was to determine if supplementation of a yeast fermentation product had an effect on the ADG, performance, and meat quality characteristics of Kathadin sheep fed a ryegrass hay based diet in drylot. Twenty-four Katahdin lambs were divided into two groups (male, n = 8; female n = 16) based on weight and gender: a control (CON) and treatment (TRT) used in a repeated block design. The lambs had a BW of 21.5 ± 2.5 kg, and concluded with a finishing weight of 36.3 ± 3.4 kg. Lambs were housed on dirt drylot with shade structures, and offered an ad libitum TMR diet was formulated to be isocaloric and isonitrogenous at 14% CP and was ryegrass hay based, and top dressed with ground corn as a carrier. The TRT received the yeast supplement at a rate of 4/g/h/d. The diet was offered at 2% of the group's body weight ad libitum. A 1-wk standardization period was conducted before the start of the study to obtain a 5% refusal rate. Orts were collected and recorded, as well as weekly feed samples were collected twice a week, and compiled for a chemical analysis for NDF, ADF, ASH, CP, and ether extract. Temperature and humidity data was also collected throughout the study. Lambs were weighed weekly with a rolling weight being used for the ADG of the lambs. Proc mixed procedures of SAS was used for data analysis. We found no statistical significance in DMI (CON=11.14 ±3.36 kg/d and TRT= 10.89 ±3.55 kg/d per group), and no statistical significance by gender (P < 0.11). There was a statistical significance (P < 0.03), for ADG per group. This suggests that there is a tendency for greater performance and ADG for lambs supplemented with a yeast fermentation product.